2008
DOI: 10.1177/002204260803800108
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Acculturation and Enculturation in Relation to Heavy Episodic Drinking and Marijuana Use in a Sample of Mexican American Serious Juvenile Offenders

Abstract: This study examines the longitudinal relations of multiple dimensions of acculturation and enculturation to heavy episodic drinking and marijuana use in a sample of 300 male, MexicanAmerican, serious juvenile offenders. We track trajectories between ages 15 and 20 and also consider the effects of participants' time spent residing in supervised settings during these years. Results showed some (although not entirely consistent) support for the hypothesis that bicultural adaptation is most functional in terms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…Previous research has shown that Latino immigrants largely identify with the integration/bicultural category in which they have integrated both culture's views into their own identity (Neto, 2002;Roccas, Horenczyk, & Schwartz, 2000;van Oudenhoven & Eisses, 1998). Further, studies have found that the extent to which an individual integrates both culture's views (i.e., integration/bicultural) is associated with better psychological outcomes when compared to those incorporating one culture (Berry, Kim, Minde, & Mok, 1987;LaFromboise, Coleman & Gerton, 1993;Losoya et al, 2008;Smokowski & Bacallao, 2007;Smokowski, Rose, & Bacallao 2008;Sullivan et al, 2007;Zarate, Bhimji, & Reese, 2005).…”
Section: Bidimensional Modelsmentioning
confidence: 99%
“…Previous research has shown that Latino immigrants largely identify with the integration/bicultural category in which they have integrated both culture's views into their own identity (Neto, 2002;Roccas, Horenczyk, & Schwartz, 2000;van Oudenhoven & Eisses, 1998). Further, studies have found that the extent to which an individual integrates both culture's views (i.e., integration/bicultural) is associated with better psychological outcomes when compared to those incorporating one culture (Berry, Kim, Minde, & Mok, 1987;LaFromboise, Coleman & Gerton, 1993;Losoya et al, 2008;Smokowski & Bacallao, 2007;Smokowski, Rose, & Bacallao 2008;Sullivan et al, 2007;Zarate, Bhimji, & Reese, 2005).…”
Section: Bidimensional Modelsmentioning
confidence: 99%
“…Pathways investigators used a subset of the Pathways sample (300 male Mexican-American offenders) to examine the relationship of cultural adaptation to patterns of heavy episodic drinking and marijuana use from ages 15 to 20 (Losoya, et al, 2008). These investigators found that bicultural adaptation (i.e., successful adaptation to both the ethnic and mainstream cultures) is related to lower substance use.…”
Section: The Pathways To Desistance Studymentioning
confidence: 99%
“…In addition, Lorenzo-Blanco, Unger, Baezconde-Garbanati, Ritt-Olson, and Soto (2012) concluded that Hispanic youth experience the process of assimilation in ways unique to them, meaning that Blacks and Whites do not go through this same social and cultural process. The authors suggested that acculturation increases these youth’s risk of delinquency, whereas enculturation protects against involvement in negative or harmful behaviors (see also Losoya et al, 2008; Maldonado-Molina, Piquero, Jennings, Bird, & Canino, 2009). This evidence highlights the importance of identifying racial/ethnic differences in exposures to negative life events and the implementation of coping mechanisms.…”
Section: Prior Literaturementioning
confidence: 99%